Численно-полевая оценка эффективности укорочения обмотки статора турбогенератора - Милых, Владимир Иванович; Полякова, Наталия Владимировна (НТУ "ХПИ", 2014)
На основе численных расчетов вращающегося магнитного поля проведена оценка турбогенератора в случаях укороченной и диаметральной обмотки статора. Сравниваемыми параметрами являются форма и гармонический состав ЭДС этой обмотки, переменная составляющая магнитного поля на поверхности ротора, пульсации электромагнитного момента.

On the basis of numerical calculations of rotating magnetic field, a turbogenerator is evaluated for cases of a shortened stator winding and a diametric one. The parameters compared are the shape and harmonic composition of the winding EMF, the alternating component of the magnetic field on the rotor surface, and the electromagnetic torque ripple.
Numerical field estimation of turbogenerator stator winding shortening efficiency
Keywords: поле магнитное; форма; состав гармонический; ротор; пульсация; момент электромагнитный; numerical-field method; turbogenerator; stator winding; shortening; time functions; electromotive force; magnetic field; rotor surface